Statistical data of special fitness of young canoeists and their comparative analysis with the incidence of Word champions - Skernevicius, J.; Dadeliene, R.; Balciunas, E.; Duonela, A. (Education. Physical training. Sport, 2004)
The aim of the work was to analyze the physical development, physical capacity and special fitness of 15-17 year old canoeist from Lithuanian Olympic reserve, to find the correlation among these indices and to compare them with the related indices of the world`s canoeists. We examined 15 canoeists, aged 15—17 years, from Lithuanian Olympic reserve and the world champions. The basic indices of physical development, single muscle contraction power, anaerobic alactic muscular power as well as usual psychomotor response time, central nervous system`s lability were determined. To assess the functional capacity of the circulatory system we employed Roufier`s test. Blood pressure was measured at rest and after 200 m of programmed work, immediately and after 3 minutes. Statistical calculations and a correlative analysis were done. The results showed that the mean values of height, body mass, hand force, muscular mass indices has been significantly lower in young canoeists than in elite Lithuanian canoeists. A correlation of these indices with special capacity is high. For the short-distance special fitness of young canoeists of significance are the high jump and AAMP indices. The psychomotor response time and central nervous system`s lability in young sportsmen were close to the related indices in powerful adult canoeists. Their relation to special power is evident. Therefore these indices can be very helpful in the selection and orientation of canoeists while choosing distances. The circulatory system`s functional capacity indices in young canoeists are considerably lower than in their adult counterparts. Special attention should be paid to the development of these functions.